2021
DOI: 10.21608/mjss.2021.213283
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation the Adverse Effects of Salinity Stress on Soybean Cultivars by Foliar Spraying of Arginine

Abstract: The present study was carried out at the experimental farm of Tag El-Ezz Agricultural Research Station (30 o 59 \ N latitude, 31 o 58 \ E longitude´), Agricultural Research Center, Dakahlia Governorate, Egypt, to study the effect of foliar spraying of arginine on four soybean cultivars under salinity stress. This experiment was laid out in a split plot design with three replicates during the two successive summer seasons of 2020 and 2021. The main plots were occupied by four soybean cultivars (Giza 111, Giza 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Expanding the available area for paper. These findings align with the observations made by Abd El-Azeiz et al (2021) [11] and Salim et al (2022) [16] , who reported notable variations in leaf area. As for intercropping systems, we notice from same table that there are significant differences between arithmetic means of intercropping systems in leaf area trait, as the single soybean treatment recorded highest average for trait, amounting to (205.25) cm 2 , while (2: 2) loading system gave lowest average for trait, amounting to (176.20).…”
Section: Results and Discussion 1 Effect Of Intercropping Systems And...supporting
confidence: 92%
“…Expanding the available area for paper. These findings align with the observations made by Abd El-Azeiz et al (2021) [11] and Salim et al (2022) [16] , who reported notable variations in leaf area. As for intercropping systems, we notice from same table that there are significant differences between arithmetic means of intercropping systems in leaf area trait, as the single soybean treatment recorded highest average for trait, amounting to (205.25) cm 2 , while (2: 2) loading system gave lowest average for trait, amounting to (176.20).…”
Section: Results and Discussion 1 Effect Of Intercropping Systems And...supporting
confidence: 92%
“…One possible explanation can be attributed to the Si ability in modifying cell wall metabolism by improving cell wall enlargement and tissue extensibility, 25 or avoiding chlorophyll damage. 14 These improvements in plant growth due to different methods of Si application were previously reported in salt-stressed sunflower plants, 21,27 faba bean, 23 cucumber, 32 sunflower, 26,30 soybean plants, 45 and cotton. 46 The results suggest that Si has the ability to improve plant growth under different salinity conditions.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, the increased seed yield under hot conditions indicates the potential of Giza 111 as a resilient crop variety for regions with high temperatures and salinity levels. The best way to increase vegetative growth, chlorophyll content, leaf relative water content, proline content and antioxidant enzyme activity was to spray arginine at a dose of 300 mg/L with Giza 111 60 . These data indicate that each of these two factors act dependently on seed yield and yield components.…”
Section: Discussionmentioning
confidence: 99%